Measurement of Radioactivity And Assessment of Radiological Hazard of Tea Samples Collected From Local Market In Bangladesh (Journal of Bangladesh Academy of Sciences, 2018)
The activity concentrations of natural radionuclides and radiological hazard indices in eleven tea samples collected from local market in Bangladesh have been analyzed by using High Purity Germanium (HPGe) Detector. The average activity concentrations of 226Ra, 232Th and 40K in tea samples have been found to be 21.21±14.04, 32.43±7.48 and 93.47 ± 43.94 Bqkg-1 respectively. The calculated absorbed dose rates due to these radioactive nuclides in tea samples have been found to vary from 26.24 nGyh-1 to 37.95 nGyh-1 and average value was 33.28 nGyh-1. The estimated outdoor annual effective dose rates varied from 38.64  µSvy-1 to 55.89 µSvy-1 with the mean value of 49.02 µSvy-1 which is less than the world average value of 1000 µSvy-1. The values of radium equivalent activity in all samples are less than the permissible maximum value of the radium equivalent activity which is 370 Bqkg-1 according to UNSCEAR 2000 report. The values of external and internal hazard indices for different samples varied from 0.16 to 0.23 with the average value of 0.20 and from 0.21 to 0.29 with an average of 0.26. The value of this index must be less than unity in order to keep the radiation hazard insignificant. It was also found that there is no artificial radionuclide (for example 137Cs) in any of the samples. The data generated in this study will provide baseline radiometric values for natural and artificial radioactivity in tea samples in Bangladesh.Journal of Bangladesh Academy of Sciences, Vol. 42, No. 2, 171-176, 2018